Leisure in the Life of the 21st Century Black Church: Re-Thinking the Gift - Steven N. Waller Ph.D. (Movement and Being: The Journal of the Christian Society for Kinesiology, Leisure and Sports Studies, 2010)
Scholarship devoted to examining the role that leisure plays in the life of the Black Church is lacking. Leisure is an important facet of congregational life in African American churches and permeates congregational dynamics on multiple levels. The purpose of this essay is to examine leisure in the life of the Black Church and posit how a healthy, theologically accurate understanding of the value of leisure can help with health and wellness promotion, community-economic development and church growth. The Black Church is defined as the eight historically Black denominations: African Methodist Episcopal, African Methodist Episcopal Zion, Christian Methodist Episcopal, Church of God in Christ, National Baptist Convention, USA, Inc., National Baptist Convention of America, National Missionary Baptist Convention, and Progressive National Baptist Convention. How the Black Church defines leisure philosophically and theologically continues to evolve. The focal points of discussion in this paper include: (1) the tension between religious tradition, leisure and the Black Church; (2) the value of leisure to the 21st century Black Church; (3) leisure as a catalyst for promoting physical activity in Black churches; and (4) social leisure as an important facet of congregational life and church growth. among African American churches. This essay also provides examples of how progressive Black churches across the United States have utilized leisure to develop health promotion programs, and to spur church growth. Finally, this paper calls for additional research specific to leisure and the Black Church along with the espousal of a meaningful theology of leisure by Black churches.
Keywords: Leisure; spirituality; recreation; black church; sport; religion